Mathematics (T) semester 1 - Tai, Pon Hoy (Pre-U STPM Text, 2019)
This books is based on new STPM syllabus. The contents fulfill the new STPM examination system requirement. It is a comprehensive reference for student who will be sitting for Mathematic (T) Paper 1 (954/1) examination at the end of the semester 1.